2016
DOI: 10.1016/j.jfma.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Citrus polyphenol for oral wound healing in oral ulcers and periodontal diseases

Abstract: The results confirm the feasibility of CP be a supplemental compound in mouthwash for treatment of periodontal diseases in dental application to improve wound healing in the mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…During dental applications of the polyphenolic compounds of these species have shown that these compounds are improved oral wound healing. Therefore, these polyphenols could be used as a supplemental compounds in mouthwash for periodontal diseases to improve wound healing in the mouth [24,25].…”
Section: Citrus Aurantifolia Swing (Rutaceae)mentioning
confidence: 99%
“…During dental applications of the polyphenolic compounds of these species have shown that these compounds are improved oral wound healing. Therefore, these polyphenols could be used as a supplemental compounds in mouthwash for periodontal diseases to improve wound healing in the mouth [24,25].…”
Section: Citrus Aurantifolia Swing (Rutaceae)mentioning
confidence: 99%
“…Another study found that using polyphenols improved wound healing in oral sores and periodontitis [ 8 ]. Wound healing occurs following disruption or damage to the normal anatomical structure and function and depends on the power of tissue regeneration, resulting in a coordinated series of cellular and molecular processes including hemostasis, inflammation, proliferative phase, angiogenesis, wound contracture, epithelialization, and matrix remodeling [ 9 ].These processes depend on homogenous functions of neutrophils, macrophages, fibroblasts, and endothelial cells that are controlled by the interaction with other cells, extracellular matrix proteins, and growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies were carried out to evaluate the antioxidant and anti-inflammatory capacity of plants on oral ulcer healing and many of them had been published (12)(13)(14). Piper sarmentosum is one of the herbaceous plants which can be found growing abundantly around Southeast Asian countries including Malaysia.…”
Section: Introductionmentioning
confidence: 99%